TINGKAT KEBUGARAN JASMANI PESERTA DIDIK KELAS X MAN 1 KOTA PADANG - Nofebra Maulana; Masrun; Padli; Heru Syarli Lesmana (Fakultas Ilmu Keolahragaan Unimed, 2026)
The problem in this study is the lack of physical fitness among students in participating in physical education classes. This study aims to determine the level of physical fitness of 10th grade students at MAN 1 Padang. This study is descriptive in nature. This research was conducted at MAN 1 Padang City. The population in this study was 345 students. The sampling technique used purposive sampling, so the sample in this study was 36 students, 14 boys and 22 girls. The test used was the Indonesian Student Fitness Test (TKSI), and the aspects observed were 1) Hand and eye coordination test 2) Vertical jump test 3) T test 4) Hand touch reaction test 5) Dipping Test 6) Beep test. The data analysis technique used was descriptive statistics. Based on the data analysis, the following conclusions were drawn: 1) The hand and eye coordination test for boys and girls was in the moderate category. 2) The vertical jump test for boys was in the moderate category, while that for girls was in the good category. 3) The T test for boys was in the good category, while that for girls was in the moderate category. 4) The hand touch reaction test for boys and girls was in the good category. 5) The dipping test for boys and girls was in the moderate category. 6) The beep test for boys and girls was in the poor category. Thus, the physical fitness level of Grade X students at MAN 1 Padang City was in the moderate category.